Progress in the mechanism of functional dyspepsia: roles of mitochondrial autophagy in duodenal abnormalities - Zhong, Kexin; Du, Xiaojuan; Niu, Yuanyuan; Li, Zhengju; Tao, Yongbiao; Wu, Yuqian; Zhang, Ruiting; Guo, Linjing; Bi, Yurong; Tang, Lijuan; Dou, Tianyu; Wang, Longde (Frontiers in Medicine, 2024)
Mitochondria are the main source of energy for cellular activity. Their functional damage or deficiency leads to cellular deterioration, which in turn triggers autophagic reactions. Taking mitochondrial autophagy as a starting point, the present review explored the mechanisms of duodenal abnormalities in detail, including mucosal barrier damage, release of inflammatory factors, and disruption of intracellular signal transduction. We summarized the key roles of mitochondrial autophagy in the abnormal development of the duodenum and examined the in-depth physiological and pathological mechanisms involved, providing a comprehensive theoretical basis for understanding the pathogenesis of functional dyspepsia. At present, it has been confirmed that an increase in the eosinophil count and mast cell degranulation in the duodenum can trigger visceral hypersensitive reactions and cause gastrointestinal motility disorders. In the future, it is necessary to continue exploring the molecular mechanisms and signaling pathways of mitochondrial autophagy in duodenal abnormalities. A deeper understanding of mitochondrial autophagy provides important